2018
DOI: 10.3389/fphar.2018.00087
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK Signaling Pathway Mediates Shuanghuanglian Injection-Induced Pseudo-allergic Reactions

Abstract: Background: Shuanghuanglian injection (SHLI) is a famous Chinese medicine used as an intravenous preparation for the treatment of acute respiratory tract infections. In the recent years, the immediate hypersensitivity reactions induced by SHLI have attracted broad attention. However, the mechanism involved in these reactions has not yet been elucidated. The present study aims to explore the characteristics of the immediate hypersensitivity reactions induced by SHLI and deciphers the role of the RhoA/ROCK signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…All parts of A. roxburghii have a long tradition use as a folk medicine to treat various ailments, with indications from one country to the other. In China, the whole plant has been used in various dosage forms such as oral liquid, spray, capsules, and its mixture to treat hepatitis, hyperliposis, tumor, chronic hepatitis B, diabetes [ 1 , 2 , 3 , 4 , 5 ] and nephritis, cystitis, myasthenia gravis, rheumatoid arthritis, febrile convulsion, cough-variant, and snakebite [ 6 ]. In Taiwan, all plant parts are frequently used as a tonic and treat hypertension, lung disease, kidney deficiency [ 7 ], cancer, and other incurable diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…All parts of A. roxburghii have a long tradition use as a folk medicine to treat various ailments, with indications from one country to the other. In China, the whole plant has been used in various dosage forms such as oral liquid, spray, capsules, and its mixture to treat hepatitis, hyperliposis, tumor, chronic hepatitis B, diabetes [ 1 , 2 , 3 , 4 , 5 ] and nephritis, cystitis, myasthenia gravis, rheumatoid arthritis, febrile convulsion, cough-variant, and snakebite [ 6 ]. In Taiwan, all plant parts are frequently used as a tonic and treat hypertension, lung disease, kidney deficiency [ 7 ], cancer, and other incurable diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the information available in the commercial instructions, SHLI is clinically recommended for use at a dosage of 60 mg/kg, which is approximately equivalent to 600 mg/kg in mice [42]. In the previous study, we showed that treatment with SHLI at 600 mg/kg could result in endothelial dysfunction and aberrant vascular leakage in mice [16]. Therefore, the minimum vascular leakage-responsive doses used in the present study, 50 mg/kg of forsythoside A and 100 mg/kg of forsythoside B, were approximately 7 and 12 times as high as their equivalent clinical dosages (7.92 and 8.58 mg/kg), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we demonstrated that SHLI could induce IgE-independent but doserelated pseudoallergic reactions by evoking histamine release, activating the RhoA/ROCK signaling pathway, and triggering increased vascular leakage [16]. This effect, at least partly, results in the hypersensitivity reactions of SHLI in the clinic.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations